RANCANG BANGUN SISTEM APLIKASI PENGADAAN BARANG DENGAN METODE DYNAMIC SYSTEMS DEVELOPMENT METHOD (DSDM) BERBASIS WEBSITE UNTUK MENUNJANG KINERJA PADA PT. MITRA BANGUNAN ABADI - Rio Maryono; Munawaroh Munawaroh (LPPM Politeknik Pratama Kendal, 2025)
This study aims to design and develop a web-based procurement system to enhance efficiency and effectiveness at PT. Mitra Bangunan Abadi. The current manual process causes delays, approval bottlenecks, and limited reporting transparency. Using the Dynamic Systems Development Method (DSDM), system development was carried out iteratively based on user needs. Needs analysis through interviews and observations identified issues such as difficulty in tracking requests, frequent approval delays, and potential data duplication. The proposed system automates procurement, streamlines approvals, and provides real-time transparency. Results show improved process speed, data accuracy, communication, and decision-making, making procurement more structured and efficient.